Simulation high-voltage triple-junction photovoltaic converters based on amorphous and microcrystalline silicon - Чеботарьов, Сергій Миколайович; Пащенко, Олександр Сергійович; Луніна, Марина Леонидівна; Ірха, Володимир Олександрович (Eastern-European Journal of Enterprise Technologies, 2013)
The design of a triple-junction thin-film photovoltaic converter with hydrogen and oxygen microcrystalline and amorphous silicon layers α-Si:H(n-i-p)/μс-Si:O(n-i-p)/μс-Si:H(n-i-p) is suggested. The physical model and the software for simulation performances of these photovoltaic converters are developed. The numerical simulation results demonstrate that efficiency of the proposed thin-film photovoltaic converters can be increased to 16 %, open-circuit voltage UOC=1.957 V, fill factor ff=78%. The analyses of the triple-junction structure’s external quantum efficiency spectral dependences shows that combining α-Si:H and μс-Si:H n-i-p junction admits to use different solar irradiation regions to expand spectral sensitivity of silicon photovoltaic converter in UV and near-IR regions. Improving the performance ensures by increasing absorptance in the visible region (λ=500-800 nm) to 40-60 % and in the near-infrared region (λ=800-1100 nm) to 75-80 %.